Foreign Bodies in the Oesophagus: The Experience of the Buenos Aires Paediatric ORL Clinic. (6th September 2010) - Chinski, Alberto; Foltran, Francesca; Gregori, Dario; Ballali, Simonetta; Passali, Desiderio; Bellussi, Luisa
Abstract : The ingestion of foreign bodies causing esophageal injuries is a common event, mostly in children's population. The aim of the present paper is to present foreign body (FB) ingestion cases observed in a five-year period at the Children's Hospital Gutierrez, Buenos Aires, Argentina and to compare the main findings with data coming from other well-known case series, already published in scientific literature. A prospective study on 320 of esophageal foreign body was carried out, with regard to age and sex distributions, type, dimensions and consistency, location, clinical presentation, removal and complications. In the majority of cases injuries happened while children were playing and in 85.3% adults were present. Children most frequently ingested coins (83.8% cases). Removal was performed in all cases under general anaesthesia, in 34 by esophageal forceps and in 286 cases by Magill hypopharyngeal forceps. Just one case showed complications, presenting esophageal perforation. The final results of this study show that injuries usually happen under adults' supervision and highlight that FBs involved in the incident belong to classes of objects not conceived for children's use and not suitable for their age. Therefore, educational strategies regarding safe behaviours have a key role in FB injuries prevention.